Primary ciliary dyskinesia (PCD) in Austria - Lesic, Irena; Maurer, Elisabeth; Strippoli, Marie Pierre Francoise; Kuehni, Claudia Elisabeth; Barbato, Angelo; Frischer, Thomas H.; Azevedo, I.; Baktai, G.; Barbato, Angelo; De Blic, J.; Bush, Andrew P.; Carlsen, K-H.; et al. (My University, 2009)
INTRODUCTION: Primary ciliary dyskinesia (PCD) is a rare hereditary recessive disease with symptoms of recurrent pneumonia, chronic bronchitis, bronchiectasis, and chronic sinusitis. Chronic rhinitis is often the presenting symptom in newborns and infants. Approximately half of the patients show visceral mirror image arrangements (situs inversus). In this study, we aimed 1) to determine the number of paediatric PCD patients in Austria, 2) to show the diagnostic and therapeutic modalities used in the clinical centres and 3) to describe symptoms of children with PCD. PATIENTS, MATERIAL AND METHODS: For the first two aims, we analysed data from a questionnaire survey of the European Respiratory Society (ERS) task force on Primary Ciliary Dyskinesia in children. All paediatric respiratory units in Austria received a questionnaire. Symptoms of PCD patients from Vienna Children's University Hospital (aim 3) were extracted from case histories. RESULTS: In 13 Austrian clinics 48 patients with PCD (36 aged from 0–19 years) were identified. The prevalence of reported cases (aged 0–19 yrs) in Austria was 1:48000. Median age at diagnosis was 4.8 years (IQR 0.3–8.2), lower in children with situs inversus compared to those without (3.1 vs. 8.1 yrs, p = 0.067). In 2005–2006, the saccharine test was still the most commonly used screening test for PCD in Austria (45%). Confirmation of the diagnosis was usually by electron microscopy (73%). All clinics treated exacerbations immediately with antibiotics, 73% prescribed airway clearance therapy routinely to all patients. Other therapies and diagnostic tests were applied very inconsistently across Austrian hospitals. All PCD patients from Vienna (n = 13) had increased upper and lower respiratory secretions, most had recurring airway infections (n = 12), bronchiectasis (n = 7) and bronchitis (n = 7). CONCLUSION: Diagnosis and therapy of PCD in Austria are inhomogeneous. Prospective studies are needed to learn more about the course of the disease and to evaluate benefits and harms of different treatment strategies.
Primäre Ziliendyskinesie in Österreich
Keywords: Bronchiectasis; Diagnosis; Epidemiology; Mucociliary clearance; Primary ciliary dyskinesia; Sinusitis; Situs inversus; Therapy